2022
DOI: 10.3390/ijms232315181
|View full text |Cite
|
Sign up to set email alerts
|

Direct In Vivo Comparison of 99mTc-Labeled Scaffold Proteins, DARPin G3 and ADAPT6, for Visualization of HER2 Expression and Monitoring of Early Response for Trastuzumab Therapy

Abstract: Non-invasive radionuclide molecular visualization of human epidermal growth factor receptor type 2 (HER2) can provide stratification of patients for HER2-targeting therapy. This method can also enable monitoring of the response to such therapies, thereby making treatment personalized and more efficient. Clinical evaluation in a phase I study demonstrated that injections of two scaffold protein-based imaging probes, [99mTc]Tc-(HE)3-G3 and [99mTc]Tc-ADAPT6, are safe, well-tolerated and cause a low level of radio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…Understanding the differences in biodistribution between different scaffold proteins should facilitate the selection of the most appropriate molecules for further clinical development. A direct preclinical in vivo comparison of [ 99m Tc]Tc-ADAPT6 and [ 99m Tc]Tc-(HE) 3- G3 revealed a significantly higher uptake of both radiopharmaceuticals in HER2-positive compared to HER2-negative tumours [ 20 ]. However, [ 99m Tc]Tc-ADAPT6 provided better discrimination between HER2-positive and HER2-negative xenografts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the differences in biodistribution between different scaffold proteins should facilitate the selection of the most appropriate molecules for further clinical development. A direct preclinical in vivo comparison of [ 99m Tc]Tc-ADAPT6 and [ 99m Tc]Tc-(HE) 3- G3 revealed a significantly higher uptake of both radiopharmaceuticals in HER2-positive compared to HER2-negative tumours [ 20 ]. However, [ 99m Tc]Tc-ADAPT6 provided better discrimination between HER2-positive and HER2-negative xenografts.…”
Section: Discussionmentioning
confidence: 99%
“…However, [ 99m Tc]Tc-ADAPT6 provided better discrimination between HER2-positive and HER2-negative xenografts. On the other hand, [ 99m Tc]Tc-(HE) 3- G3 was capable of sensing the decrease in HER2 expression in response to trastuzumab therapy, which would be suitable for monitoring the early response to such treatment [ 20 ]. Still, there are numerous differences in the physiology and biochemistry of animal models and humans, and animal studies do not reflect all the interactions of scaffold proteins with targets that are expressed in normal tissues or their off-target interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Albumin-binding domain-derived affinity proteins (ADAPTs) are engineered scaffold proteins, which are small (5–7 kDa), and display high affinity and specificity to selected targets [ 19 ]. In preclinical studies, an ADAPT labelled with 99m Tc ([ 99m Tc]Tc-ADAPT6) demonstrated efficient differentiation of HER2-positive and HER2-negative tumours, and low uptake in tissues, which frequently harbour breast cancer metastases [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the process of an ideal TRT, internally administered radionuclides will migrate specifically to the tumor region to precisely exert their cytotoxicity without any significant detrimental effects on the surrounding normal tissues (29, 30), as exemplified by a famous case of administration of 131 I to patients with thyroid carcinoma (31)(32)(33)(34)(35). Specific targeting can be achieved through antigen-antibody recognition (36,37), ligand-receptor interaction (38), or the interaction between certain biomolecules and unique biomarkers on the surface of tumor cells based on their high affinity (22). As such, the required dosage of radionuclide used in the treatment can be much less, which will significantly minimize the unnecessary exposure of patients to radiation both temporally and spatially.…”
mentioning
confidence: 99%